Good and Correct Indonesian Language Counseling in Developing Children's Language Ethics in the Digital Era - Bisarul Ihsan; Anwar Sholikhin; Wahyu Dini Septiari (Shof Literacy Community, 2024)
The digital era has brought significant changes in the way children communicate, including in the use of Indonesian. However, easy access to technology and social media often has an impact on the decline in language ethics, such as the use of impolite words, grammatical errors, and the tendency to adopt language that is not in accordance with norms. This study aims to analyze the effectiveness of good and correct Indonesian language counseling in building children's language ethics in the digital era. The research method used is a qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The counseling is designed to provide an understanding of the importance of language ethics, the correct way to use Indonesian, and practical strategies to deal with the influence of digital language. The results of the study showed that counseling was able to increase children's awareness of the importance of language ethics, improve their communication patterns, and motivate them to use good and correct Indonesian in everyday interactions, including on social media. In addition, counseling also plays a role in shaping children's character to better appreciate cultural values and social norms through the use of language.